71‐4: Distinguished Paper: OLED Display Incorporating Organic Image Sensor. Issue 1 (29th May 2019) - Kamada, Taisuke; Hatsumi, Ryo; Watanabe, Kazunori; Kawashima, Susumu; Katayama, Masahiro; Adachi, Hiroki; Ishitani, Tetsuji; Kusunoki, Koji; Kubota, Daisuke; Yamazaki, Shunpei
Abstract : We have developed a display that incorporates an organic image sensor formed in the same pixel as OLEDs through side‐by‐side patterning. The potential applications of this display include touch sensing, scanning, and fingerprint identification at any location on the entire display screen, without the necessity of an external module.